ANALISIS MANAJEMEN BIMBINGAN KONSELING DALAM PENINGKATAN PRESTASI BELAJAR SISWA - Hendri Almawijaya (Manajer Pendididikan, 2015)
The purpose of this study is to describe the management, actuating, evaluation, and problems of counseling guideline and students' academic and nonacademic learning achievementat government junior high-schools in Lubuklinggau. The research method was analytic descriptive. Subject of research is the principal, vice principal areas of student and teacher guidance and counseling. The results of the research show that not all secondary school run the planning, implementation guidance and counseling as well, constraints in the implementation of counseling include shortage of guidance services and infrastructure limitations, the evaluation of theimplementation of the counseling is done monthly, semester and yearly. With the conclusion that guidance and counseling services can help improve student achievement in schoolsKeywords: management, guidance and counseling, improving, learning achievement